An oncolytic herpes simplex virus armed with IL-12 for treatment of preclinical glioblastoma - Joseph W. Jackson; Bonnie L. Hall; Chaim Sneiderman; Amy Webb; Trevor J. Hancock; Marina Vlasyuk; Lisa Bailey; Molly Xiaokui; Isaac H. Solomon; Keith Ligon; William F. Goins; Gary Kohanbash; et al. (Molecular Therapy: Oncology)
Glioblastoma (GBM) is a devastating brain cancer with a 5-year survival rate of ∼5% despite current treatment regimens. Multiple oncolytic herpes simplex viruses (oHSV) have been designed for GBM therapy, but clinical trials have thus far met with limited success. A potential reason for this lack of efficacy is the immunosuppressive tumor microenvironment (TME) of GBM. Here we used an oHSV (KOS strain) armed with interleukin (IL)-12 (oHSV:IL-12) in an attempt to overcome this immunosuppression and analyzed the immunological and therapeutic impact in murine CT2A and GL261N4 orthotopic syngeneic glioma models. Unarmed oHSV failed to enhance survival in animals bearing syngeneic GBM tumors. However, oHSV:IL-12 induced significant and durable therapeutic benefits. TME interrogation following oHSV:IL-12 therapy revealed a significant accumulation of macrophages and cytotoxic T cells. Further investigation using single cell RNA-sequencing of GL261N4 tumors treated with either oHSV or oHSV:IL-12, indicated that oHSV:IL-12 induced robust macrophage accumulation within the TME and encouraged T cell receptor clonotype expansion compared to controls. These data point to the propensity of the IL-12 transgene to manipulate the myeloid compartment within the glioma TME, promote T cell expansion, and improve survival.